In with the Big, Out with the Small: Removing Small-Scale Reservations in India - Martin, Leslie A.; Nataraj, Shanthi; Harrison, Ann E. (American Economic Review, 2017)
An ongoing debate in employment policy is whether promoting small and medium enterprises creates jobs. We use the elimination of small-scale industry (SSI) promotion in India to address this question. For 60 years, SSI promotion in India focused on reserving certain products for manufacture by small and medium enterprises. We identify the consequences for employment growth, investment, output, productivity, and wages of dismantling India's SSI reservations. We exploit variation in the timing of de-reservation across products and also measure the long-run impact of national SSI policy changes using variation in pretreatment exposure at the district level. Districts more exposed to de-reservation experienced higher employment and output growth. Entrants into the de-reserved product spaces and incumbents that were previously constrained by the size restrictions drove the increase in growth. The results suggest that dismantling India's SSI policies encouraged overall employment growth. (JEL E24, L25, L53, L60, O14, O25)